Standardization research in information technology new perspectives - Jakobs, Kai 1957- (Gale virtual reference library, 2008)
"This book amasses cutting-edge research on the application of standards in the market, covering topics such as corporate standardization, linguistic qualities of international standards, the role of individuals in standardization, and the development, use, application, and influence of information technology in standardization techniques"--Provided by publisher.